Status quo and future directions of facility management: a bibliometric – qualitative analysis - Li, Yongkui; Zhang, Yan; Wei, Jianjun; Han, Yilong (International Journal of Strategic Property Management, 2019)
Facility management (FM) has received extensive attention from practitioners and researchers. While FM is continuously maturing as a scientific discipline and relevant studies are constantly growing, there are no holistic reviews of current research. The information in previous studies is generally scattered, and existing literature reviews mostly focused on specific aspects of FM. It is necessary for researchers and practitioners to obtain a thorough view of the current status in the FM field and future development trends that have been summarized and discussed in depth. Using a bibliometricqualitative analysis, a total of 724 academic journal papers on FM, between 1995 and 2018, were reviewed. A number of the latest advancements and emergent trends were identified based on knowledge maps in FM, including changing circumstances, enhancing information technology, all-around facility manager, strategic performance management, sustainable FM and innovative FM practice. It is hoped that this review can help researchers understand the current body of FM knowledge. The future directions were also highlighted in this study to help researchers identify areas where research is most needed. This study could also help practitioners to address upcoming challenges in the FM field.